ECG Artifact by a Spinal Cord Neurostimulator: A Case Report - Shyla Gupta; Cathy Shaw; Sohaib Haseeb; Adrian Baranchuk (University Library System, University of Pittsburgh, 2020)
Background: Neurostimulator devices produce electrical oscillations that may prevent accurate diagnosis of an ECG. The Case: We present the case of a 68-year-old man who came to the emergency department with chest pain and a spinal cord neuromodulator device in situ to treat his polymyalgia rheumatica. A 12-lead ECG was obtained to determine the cause of the chest pain, and atrial fibrillation was wrongly diagnosed. Conclusion: This case reiterates the value of recognizing this uncommonly encountered ECG artifact to avoid unnecessary mistakes in interpretation of heart rhythms.